Fama-French Five Factor Model: Evidence from Turkey - Acaravci, Songül Kakilli; Karaomer, Yunus (International Journal of Economics and Financial Issues, 2017)
The aim of this study is to test the validity of the Fama-French Five Factor Model (FF5F) in Borsa Istanbul (BIST) during the 132-month period between July 2005 and June 2016. Therefore, the excess returns of 14 different intersection portfolios constructed on the basis of size, market to book ratio, profitability and investment factors have been used during period between July 2005 and June 2016. Our results show that there is no pricing error according to result of Gibbons, Ross, and Shanken (1989) GRS-F test of FF5F. Hence, FF5F seems to be valid in the BIST. In addition, FF5F appear to explain variations on excess portfolio returns. Keywords: CAPM, Fama-French Five Factor Model, Asset Pricing Models, Time Series. JEL Classifications: C19, D53, G14